2018
DOI: 10.1371/journal.pone.0194185
|View full text |Cite
|
Sign up to set email alerts
|

HIV induces production of IL-18 from intestinal epithelial cells that increases intestinal permeability and microbial translocation

Abstract: Interleukin-18 (IL-18) is a pleiotropic cytokine of the IL-1 family with multiple context dependent functions. We and others have shown that HIV infection is accompanied by increased circulating levels of IL-18 along with decreased levels of its antagonist, Interleukin-18 Binding Protein (IL-18BP). The infection is also accompanied by intestinal inflammation and decreased intestinal integrity as measured by intestinal permeability, regeneration and repair. However, little is known concerning the relation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 87 publications
5
15
0
Order By: Relevance
“…To our knowledge, this is the first study that investigate gut inflammation through cytokine levels with a noninvasive approach in HIV+ patients. Other groups have already reported high levels of IL-18, IL-1β, and IL-8 in gut biopsies from HIV+ patients; in this study, it was proposed that the IL-18 production is induced on intestinal epithelial cells by HIV which promotes intestinal permeability and microbial translocation [42]. Even though our result are similar to this research, this highlights the importance of measuring this biomarker at different anatomical compartments [7].…”
Section: Discussionsupporting
confidence: 82%
“…To our knowledge, this is the first study that investigate gut inflammation through cytokine levels with a noninvasive approach in HIV+ patients. Other groups have already reported high levels of IL-18, IL-1β, and IL-8 in gut biopsies from HIV+ patients; in this study, it was proposed that the IL-18 production is induced on intestinal epithelial cells by HIV which promotes intestinal permeability and microbial translocation [42]. Even though our result are similar to this research, this highlights the importance of measuring this biomarker at different anatomical compartments [7].…”
Section: Discussionsupporting
confidence: 82%
“…The inflammasome IL-1 and IL-18 cytokines could play an important role in orientating the mucosal immune response [28][29][30]. IL-18 seems predominant in the setting of HIV-1 infection [16,17]. We found increased plasma levels of IL-18, but not of IL-1, in the treated HIV-1-infected individuals included in the present study.…”
Section: Discussionsupporting
confidence: 45%
“…57,58 IL-18 also increases gut permeability through decreasing the expression of tight junction proteins or occludin phosphorylation. 59,60 These results support the notion that increased numbers of mast cells and an increased degree of mast cell activation are linked to enhance intestinal permeability in individuals with IBS. Consistent with these findings, we found that MS increased the number of mast cells and activated mast cells to release tryptase.…”
Section: Discussionsupporting
confidence: 76%
“…Treatment with anti‐IL‐6 antibody counteracts increased gut permeability and alleviates IBS‐like symptoms . IL‐18 also increases gut permeability through decreasing the expression of tight junction proteins or occludin phosphorylation . These results support the notion that increased numbers of mast cells and an increased degree of mast cell activation are linked to enhance intestinal permeability in individuals with IBS.…”
Section: Discussionsupporting
confidence: 67%